ANALISA PENGAMBILAN KEPUTUSAN UNTUK MENENTUKAN SUBKONTRAKTOR SPESIALIS DENGAN METODE TOPSIS - Ladika .; Heru Bayuaji Sanggoro (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2023)
ABSTRACT The building construction sector is a complex industry, so it is necessary to split the work and divide (deliver) it to subcontractors. In determining these subcontractors, stakeholders are faced with many and various methods in making decisions so that the selection of subcontractors can be determined optimally. This study analyzes and compares the two MADM TOPSIS methods. This research takes a case study of the subcontractor selection process carried out by the main contractor at PT. Cipta Griya Semesta. This study consists of 4 alternative subcontractors with 6 assessment criteria with the criteria of general aspects, financial aspects, technical aspects, managerial aspects, work safety aspects and reputation aspects. Based on the ranking results using these 2 methods, subcontractor D will be selected to help carry out the ongoing project. Keyword: Topsis, Subcontractor, Construction